2008
DOI: 10.1111/j.1740-8261.2008.00349.x
|View full text |Cite
|
Sign up to set email alerts
|

Osteoradionecrosis and Radiation Induced Bone Tumors Following Orthovoltage Radiation Therapy in Dogs

Abstract: Osteoradionecrosis and radiation-induced bone tumors are rare complications of radiation therapy. Little information regarding these complications is available in veterinary medicine. We characterized these complications and investigated risk factors in 119 dogs (122 sites) that received definitive orthovoltage radiation therapy to appendicular sites. Long-term survival was expected in all dogs. The complications of interest were osteoradionecrosis and secondary bone tumor, evaluated radiographically, histopat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 34 publications
5
40
1
Order By: Relevance
“…[63][64][65] One canine study reported osteosarcomas developing in almost 10% of dogs followed for 1.2 to 6.4 years after high-dose radiation therapy. 66 So although we remain concerned regarding the occurrence of these tumors, the evidence so far strongly suggests they are linked to the irradiation, not the SIV gene transfer vector. The development of effective nonmyeloablative, nonmutagenic, and less toxic conditioning regimens, particularly for nonmalignant target diseases, is crucial for any wide application of gene therapy targeting HSCs.…”
Section: Discussionmentioning
confidence: 99%
“…[63][64][65] One canine study reported osteosarcomas developing in almost 10% of dogs followed for 1.2 to 6.4 years after high-dose radiation therapy. 66 So although we remain concerned regarding the occurrence of these tumors, the evidence so far strongly suggests they are linked to the irradiation, not the SIV gene transfer vector. The development of effective nonmyeloablative, nonmutagenic, and less toxic conditioning regimens, particularly for nonmalignant target diseases, is crucial for any wide application of gene therapy targeting HSCs.…”
Section: Discussionmentioning
confidence: 99%
“…While the aetiology of osteosarcoma is still uncertain in dogs and humans, several contributing factors have been suggested. Factors such as ionizing radiation, genetics, bone tumour viruses, chemicals, chronic irritation due to fractures repaired by metallic implants, bone infarcts, skeletal diseases or disorders as well as body size and sex are believed to be involved in pathogenesis …”
Section: Aetiologymentioning
confidence: 99%
“…While the aetiology of osteosarcoma is generally unknown in both dogs and humans, a proposed association with ionizing radiation has been reported with oral and maxillofacial osteosarcomas . Other reported possible aetiologies include genetics, pre‐existing bone disease, trauma, bone viruses and metallic bone implants …”
Section: Introductionmentioning
confidence: 99%
“…45 Additionally, long-term use of bone antiresorptives is often complicated by jaw osteonecrosis while non-oral bones are spared. 46 Since dogs readily develop jaw osteoradionecrosis, 47, 48 it is not unlikely that they may be susceptible to the same pathological features as humans because dogs are exposed to similar external and environmental factors as humans.…”
Section: Discussionmentioning
confidence: 99%